Subsurface Structure Analysis for Determining the Slip Surface of Landslides Using the Wenner Resistivity Geoelectrical Method in Kokap, Kulon Progo: Analisis Struktur Bawah Permukaan untuk Penentuan Bidang Geser Longsor Menggunakan Metode Geolistrik Resistivitas Wenner di Kokap, Kulon Progo - Prihatin, Rezal; Fikri Niyartama, Thaqibul (Sunan Kalijaga Journal of Physics, 2025)
Slope failures frequently occur in hilly regions, particularly during periods of intense rainfall. At the end of 2022, such an event affected a residential area in Hargomulyo Village, Kulon Progo. Mitigation efforts against similar hazards can be implemented through mapping of landslide-prone zones, one of which involves identifying the rock layers that act as the slip surface. This study employs the geoelectrical resistivity method with a Wenner configuration to characterize the subsurface structure based on variations in electrical resistivity of soil and rock. Data acquisition was conducted along four survey lines located within an andesitic intrusion formation composed of hypersthene–andesite to trachyandesite rocks. The modeling results indicate three main layers: surface soil with resistivity values below 54.4 Ωm, clay mixed with weathered andesite ranging from 54.4 Ωm to 141 Ωm, and intact andesite bedrock exceeding 141 Ωm. Correlation with the Geological Map of Yogyakarta Sheet (Rahardjo et al., 1995) confirms that the potential slip surface corresponds to the weathered andesite–clay zone developed along the contact between the Andesite Intrusion and the Kebobutak Formation. This transition layer, acting as a mechanically weak zone, controls slope stability in the study area. The presence of a local north–south fault may further increase groundwater infiltration and pore pressure above the impermeable andesite layer, promoting slope movement during heavy rainfall. These results emphasize that integrating resistivity interpretation with geological mapping provides a more comprehensive understanding of landslide mechanisms and supports hazard mitigation efforts in andesitic terrains of Kulon Progo.